У пошуках Юрія Федьковича: маловідомі листи Михайла Драгоманова до Степана Смаль-Стоцького - Ковалець, Лідія; Kovalets, Lidija (Східноєвропейський національний університет ім. Лесі Українки, 2014)
В основі статті – першопублікація та коментування тематично пов’язаних із Ю. Федьковичем двох епісто-лярних звернень М. Драгоманова до С. Смаль-Стоцького, що зберігаються в Центральному державному істо-ричному архіві України у м. Львові. The article’s purpose is the first publication and commenting of two epistolary appeals from M. Drahomanov to S. Smal’-Stoc’kyj, primary sources of which are located in Central State Historical Archives in L'viv. The mentions about J. Fed’kovych in these letters are interlaced with the spectrum of actual primarily for Galicia and Bukovyna social and political, moral and spiritual, purely scholarly, philological problems, which worried M. Drahomanov and were discussed in polemical manner, usual for him. A huge preoccupation with these problems, the perception of them as urgent, the efforts to help the cause with his own experience largely explain why M. Drahomanov postponed writing of the promised S. Smal’Stoc’kyj special memoires about one of the greatest Ukrainian poets. Hovever, the letter, containing interesting information, that concerns J. Fed’kovych, hold the image of the memoirist himself, this thoughts and ideals.
Looking for Fed’koych: Little Known Letters from Myhajlo Drahomanov to Stepan Smal’-Stoc’kyj
Keywords: М. Драгоманов; Ю. Федькович; С. Смаль-Стоцький; лист; автограф; мемуари; M. Drahomanov; J. Fed’kovych; S. Smal’-Stoc’kyj; letter; autograph; memoires